(3TaGA GdZQGe HCNHGQ GdHdO GdMQGes - (3eMeO Hf CMeO Hf Ydj, Jbj GdOjf, CHh GdWjH Gdecqj GdMSfj, J (B832 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd ecI GdeTQaI CYXe GdHdGO TCfkG s
(3BNQgG (B:s
(3hQVj Gddg Yf Bdg hCUMGHg MeGI GdESdGe hMSHfG Gddg hfYe Gdhcjd s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B331 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B300s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B172 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B258 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs